Evidence for the efficacy of Tai Chi for treating rheumatoid arthritis: an overview of systematic reviews - Imoto, Aline Mizusaki (2021)
BACKGROUND: Rheumatoid arthritis (RA) is a chronic disease with higher prevalence among women aged between 30 and 50 years and general prevalence of 1% worldwide. Interventions promoting improvement of quality of life for individuals with RA are required. Tai Chi appears to be a low-cost alternative, with studies showing positive results from this technique. However, regarding aspects of RA such as pain and sensitivity, studies remain inconclusive. OBJECTIVES: To compare the effectiveness of the Tai Chi method for treating patients diagnosed with rheumatoid arthritis, among systematic reviews. DESIGN AND SETTING: Overview of systematic reviews with Cochrane and non-Cochrane methodology. METHODS: Systematic reviews involving quasi-randomized and randomized clinical trials (RCTs) on use of Tai Chi, with no restrictions regarding the date and language of publication, were included. RESULTS: Three systematic reviews were included. The effects of Tai Chi associated with education and stretching exercises versus education and stretching were evaluated in these reviews. They showed that improvements in the variables of mood, depression and functional index were associated with use of Tai Chi. CONCLUSIONS: The findings suggest that clinical improvement was achieved, although not statistically significant with regard to pain and disease pattern, as assessed using the ACR20 measurement. Improvements relating to disability and quality of life were also seen. There was a low level of evidence and therefore caution in data analysis is recommended. The three studies included showed poor reliability for providing an accurate and complete summary of use of Tai Chi among people diagnosed with rheumatoid arthritis. PROSPERO: CRD42019125501.